Pelawat dari University of Stratchlyde [fotograf] - Universiti Teknologi Malaysia
Datuk Dr Ahmad Zaharudin bin Idrus -- Prof. Dr. Abu Azam bin Md. Yassin -- Prof. Dr. Bahrom bin Sanugi -- Prof. Dr. Zainai bin Mohamed